a Gaya Komunikasi Budaya Dedi Mulyadi Dalam Mewujudkan Jabar Istimewa - Alfikri, Muchsin (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
Dedi Mulyadi recorded history as being elected Governor of West Java by winning the highest number of votes. Based on the West Java KPU recapitulation meeting, the pair Dedi Mulyadi – Erwan were determined to win with 14,130,192 votes or 62 percent. Dedi Mulyadi's victory was inseparable from the cultural communication style he used either during the campaign or long before the campaign started. This paper will elaborate on Dedi Mulyadi's communication style with the Sundanese cultural background that he applied to create Special West Java. By using qualitative research methods with a literature study approach and in-depth interviews, this paper concludes that Dedi Mulyadi has succeeded in winning the sympathy of the West Java public in the 2024 West Java gubernatorial election by applying a unique, friendly and down-to-earth Sundanese cultural communication style.